Clustering EU countries by the level of information and communication technologies development - Vladimir Bilozubenko; Maxim Korneyev; Serhii Ivantsov; Vadym Yakovenko; Fedir Zhuravka; Dmytro Shchytov; Mykola Nahorianskyi (Problems and Perspectives in Management)
The development and wider use of information and communication technologies (ICT) are at the core of the EU’s strategic course to intensify digital transformation. This is complicated by significant differences between EU member states in this area, the alignment of which is becoming an important task for supranational policy. The paper, therefore, aims to cluster EU countries by their ICT development level and identify key differences. A dataset was generated based on 18 relative ICT development indicators used in the ICT Development Index and the Digital Economy and Society Index. In the first stage, based on the k-means method, the EU countries were divided into three clusters, which characterize their differences in the ICT development level. Then, using the decision tree method, indicators were identified that absolutely distribute the resulting clusters, confirming their specificity. The parameters that reflect the most significant differences between EU countries in ICT development include individuals using the Internet, active mobile broadband subscriptions per 100 inhabitants, mobile data and voice high-consumption basket price, fixed-broadband Internet basket price, ICT graduates, fiber to the premises coverage, mobile broadband take-up, and 5G spectrum. This has demonstrated the critical importance of the spread and availability of the Internet, mobile technologies, and human resources for intensifying digital transformations within the EU. The results can be used in supranational policies to support the development of ICT and digital transformations and also serve as a guide in ensuring digital progress in individual member countries.